A REVIEW ON CARISSA CARANDASǧPHYTOCHEMISTRY,ETHNOǧPHARMACOLOGY, AND MICROPROPAGATION AS CONSERVATION STRATEGY - Singh, Akansha; Uppal, Gursimran Kaur (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Carissa carandas is a useful food and medicinal plant of India, found to be widely distributed throughout subtropical and topical regions. The plant has been used as a traditional medicinal plant over thousands of years in the Ayurvedic, Unani, and Homoeopathic system of medicine. Traditionally, whole plant and its parts were used in the treatment of various ailments. The major bioactive constituents, which impart medicinal value to the herb, are alkaloids, flavonoids, saponins and large amounts of cardiac glycosides, triterpenoids, phenolic compounds and tannins. Roots were reported to contain volatile principles including 2-acetyl phenol, lignan, carinol, sesquiterpenes (carissone, carindone), lupeol, Î²-sitosterol, 16Î²-hydroxybetulinic acid, Î±-amyrin, Î²-sitosterol glycoside, and des-Nmethylnoracronycine, whereas leaves were reported to contain triterpenoid constitutes as well as tannins. While, fruits have been reported to contain carisol, epimer of Î±-amyrin, linalool, Î²-caryophyllene, carissone, carissic acid, carindone, ursolic acid, carinol, ascorbic acid, lupeol, and Î²-sitosterol. Ethnopharmacological significance of the plant has been ascribed due to anti-cancer, anti-convulsant, anti-oxidant, analgesic, anti-inflammatoryAQ1, anti-ulcer, anthelmintic activity, cardiovascular, anti-nociceptive, anti-diabetic, antipyretic, hepatoprotective, neuropharmacological, and diuretic activities, antimicrobial activities and cytotoxic potentials, in-vitro anti-oxidant, and DNA damage inhibition, and constipation and diarrheal activities. The review also dealt with describing micropropagation strategies for effective conservation of this important food and medicinal plant. The review has been written with the aim to provide a direction for further clinical research to promote safe and effective herbal treatments to cure a number of diseases.